White matter integrity alterations in post‐traumatic stress disorder. Issue 3 (19th December 2017) - O'Doherty, Daniel C.M.; Ryder, Will; Paquola, Casey; Tickell, Ashleigh; Chan, Charles; Hermens, Daniel F.; Bennett, Max R.; Lagopoulos, Jim
Abstract: Post‐traumatic stress disorder (PTSD) is a debilitating condition which can develop after exposure to traumatic stressors. Seventy‐five adults were recruited from the community, 25 diagnosed with PTSD along with 25 healthy and 25 trauma‐exposed age‐ and gender‐matched controls. Participants underwent clinical assessment and magnetic resonance imaging. A previous voxel based morphometry (VBM) study using the same subject cohort identified decreased grey matter (GM) volumes within frontal/subcortical brain regions including the hippocampus, amygdala, and anterior cingulate cortex (ACC). This study examines the microstructural integrity of white matter (WM) tracts connecting the aforementioned regions/structures. Using diffusion tensor imaging, we investigated the integrity of frontal/subcortical WM tracts between all three subject groups. Trauma exposed subjects with and without PTSD diagnosis were identified to have significant disruption in WM integrity as indexed by decreased fractional anisotropy (FA) in the uncinate fasciculus (UF), cingulum cingulate gyrus (CCG), and corpus callosum (CC), when compared with healthy non‐trauma‐exposed controls. Significant negative correlations were found between total Clinician Administered PTSD scale (CAPS) lifetime clinical subscores and FA values of PTSD subjects in the right UF, CCG, CC body, and right superior longitudinal fasciculus (SLF). An analysis between UF and SLF FA values and VBM determined rostral ACC GM values found a negative correlation in PTSD subjects. Findings suggest that compromised WM integrity in important tracts connecting limbic structures such as the amygdala to frontal regions including the ACC (i.e., the UF and CCG) may contribute to impairments in threat/fear processing associated with PTSD.